Comparison between connective tissue graft and xenogeneic acellular dermal matrix to treat single gingival recession: A data reanalysis of randomized clinical trials - Miguel, Manuela Maria Viana [UNESP] (2022)
Objectives: There are few studies comparing xenogeneic acellular dermal matrixes (XDMs) with connective tissue graft (CTG) to treat single gingival recession (GR). The present study involved a reanalysis of previous studies and comparison of CTG or XDM to treat single RT1/GR. Materials and methods: Fifty patients from three previous randomized clinical trials treated either by CTG (n = 25) or XDM (n = 25) were evaluated after 6-month. Clinical, patient-centered, and esthetic parameters were assessed. Pearson's correlation and regression analyses were also performed. Results: Greater recession reduction (RecRed), percentage of root coverage (%RC), and complete root coverage (CRC) were observed in the CTG group (p ≤ 0.02). Gingival thickness (GT) and keratinized tissue width (KTW) gains were higher in the CTG group. The CTG group showed better esthetic at 6-month. Logistic analyses reported that GT([OR] = 1.6473) and papilla height (PH) (OR = 8.20) are predictors of CRC. GT*XDM interaction was a negative predictor of CRC (OR = 7.105−5). GT at baseline acted as a predictor of RecRed in both groups (p = 0.03). The XDM graft impacted RecRed and %RC negatively. Baseline PH was a predictor of %RC for both grafts. Conclusion: CTG was superior for treating RT1/GR, providing better root coverage outcomes and tissue gains over time. GT, PH, and graft type were classified as predictors of CRC. Clinical significance: CTG presented better outcomes to treat single RT1 gingival recession when compared to the XDM.